#TITLE_ALTERNATIVE# - ARIANIE (NIM 20599037), LUCY
In the year 2000, the average of palm cultivation areal in Indonesia covers 2,5 billion ha which produces 2,85 million ton dry weight of palm empty bunch (TKS). TKS still contains lignin, a phenolic polymer which has function as interfiber adhesive in plant and strengthen the branch which support the tree flat has height more than 10 m to stand still strongly. In the other hand, the production of phenol formaldehyde adhesive using phenol compounds derived from fuel, resulting prize fluctuative along with the prize of global world fuel. This reason basically became the purpose of the research which aims is to determine how far lignin and its derivatives could replace phenol in production of phenol formaldehyde adhesive which examined on the production of plywood. The technique covers lignin isolation from black liquor pulp of TKS organosolv process, lignin sulfonation, characterization of lignin and lignosulfonates, lignosulfonate fractionation and determination of molecular weight distribution using viscometer. The application of lignin and lignosulfonates to produce phenol formaldehyde which the presentage of phenol replacement of 10 - 60 % and examination of streching strength of adhesive. The lignin isolation using variation dillution achieved optimum condition for isolation at the ratio of black liquor water = 1 : 7 with 49,6 % lignin recovery and 86,78 % purity. UV and IR spectra of lignin showed the similar height compared to UV and IR spectra standar. Sulfonation of 1 g lignin in NaHSO3 at pH 5 and 100oC for 4 hours produces 2,55 g lignosulfonates which purity is 75,24 %. The UV & IR spectra of lignosulfonate showed similar spectrum compared to the standar. The fractionation of lignosulfonate utilized sephadex G-100 by size eclusion chromatography (SEC) method. The five fraction remain was examined by viscometer to obtain the molecular weight relative M= 4389; 5179; 6859; 29.110 dan 35,672. these lignin and lignosulfonate was applied as binder along with phenol formaldehyde. The result of streching tensile examination using autograph shimadzu at 250 Kgf showed the streching tensile for 10, 20, 30, 40, 50 and 60 % of phenol replacement are : 62,7 ; 212,9 ; 286,2 ; 304,4 ; 1480 dan 164,6 Kpa, respectively. In the phenol replacement using 10, 20, 30, 40, 50 and 60 % lignosulphonate resulting the streching tensile of 82,3 ; 226,0 ; 240,4 ; 414,2; 419,4 dan 81,0 Kpa. When phenol replacement using 10, 20, 30, 40, and 50 % with lignosulfonate fractionated resulting the streching tensile 304,4 ; 241,7 171,2; 86,2 ; dan 35,3 Kpa, respectively. As comparison the strength of phenol formaldehyde standard is 356,7 Kpa.